Nonlinear Modal Analysis of Vibrating Systems with Limited Power Supply - Piccirillo, V.; Tusset, A. M.; Balthazar, Jose Manoel [UNESP]; Martinez, A. G. (Springer Nature, 2022)
Nonlinear modal analysis is a powerful technique that allows a better understanding of the nonlinear dynamic behavior of mathematical models with few degrees of freedom. Nonlinear modes have emerged as a natural extension of linear modes for systems with large oscillation amplitudes. This chapter applies the technique of nonlinear normal modes analysis in a nonlinear Duffing oscillator driven by a limited (non-ideal) power source. Results show that the use of nonlinear modal analysis allows the description of the complex behavior of the system, resulting from the nonlinearities considered.